1985
DOI: 10.1104/pp.78.1.183
|View full text |Cite
|
Sign up to set email alerts
|

Water Transport in the Midrib Tissue of Maize Leaves

Abstract: Water movement across plant tissues occurs along two paths: from cell-to-cell and in the apoplasm. We examined the contribution of these two paths to the kinetics of water transport across the parenchymatous midrib tissue of the maize (Zea mays L.) leaf. Water relations parameters (hydraulic conductivity, Lpr, cell elastic coefficient, e; half-time of water exchange for individual cells, T,,2) of individual parenchyma cells determined with the pressure probe varied in different regions of the midrib. In the ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
2

Year Published

1986
1986
2011
2011

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 19 publications
4
14
2
Order By: Relevance
“…Lp px not only reflects the permeability of tissue to water, but also the resistance by yielding walls to the growth-induced water flux (Lockhart, 1965). This could also explain the discrepancy between our own estimation and those published by Steudle & Boyer (1984) and Westgate & Steudle (1985).…”
Section: Radial Hydraulic Conductivity and Water Deposition Rate Aloncontrasting
confidence: 56%
See 1 more Smart Citation
“…Lp px not only reflects the permeability of tissue to water, but also the resistance by yielding walls to the growth-induced water flux (Lockhart, 1965). This could also explain the discrepancy between our own estimation and those published by Steudle & Boyer (1984) and Westgate & Steudle (1985).…”
Section: Radial Hydraulic Conductivity and Water Deposition Rate Aloncontrasting
confidence: 56%
“…2), Lp px was close to 6.5 mmol s −" m −# MPa −" . This is about five times lower than values reported in growing sections of soybean hypocotyls (37p24 mmol m −# s −" MPa −" ) by Steudle & Boyer (1984), and about 70 times lower than values reported in midrib tissue of mature maize leaves (494p311 mmol m −# s −" MPa −" ) by Westgate & Steudle (1985). Nevertheless, these authors concluded that the method they used probably largely resulted in an overestimation.…”
Section: Radial Hydraulic Conductivity and Water Deposition Rate Aloncontrasting
confidence: 48%
“…One path may present much more resistance to flow than the other, and the path taken may depend on the nature of the force driving water movement. In corn midrib, for example, when the driving force is osmotic (as in open pulvini), water movement is confined to the cell-to-cell route; when a pressure gradient is present (as in closed pulvini), a much more rapid, apoplastic route becomes available (26 Hydrostatic Pressure. In order for a pulvinus, a nongrowing organ, to close, P must increase in the flexor relative to the extensor.…”
Section: Discussionmentioning
confidence: 99%
“…Nonami and Boyer, 1990). An increase in P, converts to a transient turgor pressure increase (Westgate and Steudle, 1985;Malone and Stankovic, 1991;Frensch and Hsiao, 1994) and then results in a transient depolarization. The application of a pressure step of 30 kPa to the root xylem converts to a AP, of only 25 kPa at position B of the pea epicotyl, which sufficed to induce a depolarization in the epidermis cells.…”
Section: Dlscusslon the Pressure Sensitivity Of Epicotyl Cellsmentioning
confidence: 99%